Understanding intelligence failure warning, response and deterrence - Wirtz, James J. (Studies in intelligence, 2017)
This collection, comprising key works by James J. Wirtz, explains how different threat perceptions can lead to strategic surprise attack, intelligence failure and the failure of deterrence. This work also offers strategies that could mitigate the occurrence of intelligence failure, strategic surprise and the failure of deterrence. This book will be of much interest to students of intelligence studies, strategic studies, security studies and IR in general.